Analisis Asuhan Keperawatan dengan Pemberian Oksigenasi dan Head Up 30° terhadap Perubahan Haemodinamik pada Pasien Cedera Kepala - Tri Sejati Kartika Dewi; Putra Agina Widyaswara Suwaryo; Muji Ageng Triyowati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2019)
Background: Head injury is a traumatic disorder of brain function accompanied or without interstitial bleeding the brain bleeding. In the world for the incidence of head injuries every year reaches 500,000 cases of the number above 10% sufferers die before reaching the hospital and more than 100,000 experience disability due to head injury. Head injuries usually involve young people (15-19 years old) and older adults over 65 years old with the male of number more often than women. Objective: Analyzing of nursing care for oxygenation and head up 30° given to clients with head injuries in the Emergency Room and High Care Unit of the RSUD Prof. Dr. Margono Soekarjo Hospital at Purwokerto. Method: The method in this study use a descriptive case study method. Nursing care results: Nursing problems that arise in these three patients are cerebral tissue perfusion disorders. The intervention that will be carried out is head up 30o and oxygenation. From the results of the implementation, it was found two of the patients experienced hemodynamic changes such as improvement in blood pressure, oxygen saturation, and breathing in patients and significant changes in consciousness during in emergency room and high care unit. This on action evaluation the secondpatient aged nineteen years old aged twentyseven years old experienced hemodynamic changes and awareness, patients aged sixty years old died. Recommendation: It is expected that the hospital provides a tool to measure cranial pressure to it knows the severity of bleeding in the brain and the patient immediately gets the right action according to the extent of brain bleeding.